2021
DOI: 10.3390/children8121124
|View full text |Cite
|
Sign up to set email alerts
|

Parenting during the COVID-19 Lockdown in Portugal: Changes in Daily Routines, Co-Parenting Relationships, Emotional Experiences, and Support Networks

Abstract: The COVID-19 pandemic challenged parental resources pertinent to coping with lockdowns. The main objective of this work was to study parenting during the COVID-19 lockdown. Specifically at focus were parental behaviors concerning key domains for the family (daily routine, co-parenting, emotional experience, and support network) and changes related to the pandemic and associated with the parents’ employment statuses. An online survey was carried out through an ad hoc questionnaire where participants completed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 27 publications
0
16
2
1
Order By: Relevance
“…The COVID-19 pandemic also changed the overall work organization and arrangements, accelerating and disrupting various trends in the work area [ 17 ]. In particular, many schools and workplaces were closed during the lockdown, so stationary work was changed to remote online, and working parents were forced to divide their time between caring for children and teleworking [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Experts assumed the transition to telework was one of the essential issues for occupational health during the COVID-19 pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The COVID-19 pandemic also changed the overall work organization and arrangements, accelerating and disrupting various trends in the work area [ 17 ]. In particular, many schools and workplaces were closed during the lockdown, so stationary work was changed to remote online, and working parents were forced to divide their time between caring for children and teleworking [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Experts assumed the transition to telework was one of the essential issues for occupational health during the COVID-19 pandemic [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a disturbed work-family balance was found among German medical doctors due to insufficient childcare when schools and preschools were closed during the pandemic [ 19 ]. The study among Portuguese-employed parents showed that, dependent on the stationary or online type of work, diverse experiences were reported during the lockdown [ 18 ]. Those working online at home reported higher levels of stress and anxiety and more difficulties in co-parenting than those working stationary (out-of-home) and unemployed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Señala De la Cruz (2020) que motivar a los hijos para estudiar en el hogar es un reto de creatividad para las familias, donde también cada uno de sus miembros se desenvuelve en los roles domésticos y laborales. Al respecto Antunes et al, (2021) plantean que los padres y madres han asumido, a la par de continuar trabajando desde casa, la responsabilidad principal de apoyar y educar a los hijos, aun cuando no tengan las condiciones socioeconómicas, culturales o educativas para realizar un apoyo eficiente de las actividades escolares. Como plantea Trejo-Quintana (2020), desde el ámbito público la pandemia ha acentuado los problemas sustanciales de la educación en México que tienen que ver, todavía, con problemas de acceso y oportunidades equitativas a la educación.…”
Section: Organización Familiar Para Apoyar En Las Actividades Escolaresunclassified